Andragogical Case Study - Borowska-Beszta, Beata (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The chapter includes methodological analyses of case studies and exemplificationsin adult education. The first part contains the origins, characteristics of the method inthe methodological context, including definitions, types of case studies, stages of researchanalysed against the background of the research project structures. After the discussionof methodological contexts, there is a part of critical analyses of four reports of qualitativecase studies on research on adulthood and adult learning carried out abroad in Westernand Oriental cultures in the USA, Scotland, Saudi Arabia and Indonesia.